Mechanism of human capital influence on household commercial insurance holding behavior—An empirical analysis based on China household finance survey (CHFS) data - Xie, Yu; Zhang, Bingbing; Yao, Yin; Chen, Xiongying; Wang, Xinyu (Frontiers in Environmental Science, 2022)
In order to better exploit the role of commercial insurance in preventing and mitigating household financial risks and improving social security, this paper explores the influence mechanism of household human capital, a special endowment resource that has potential influence on households’ cognitive and behavioral decisions on commercial insurance, by constructing a structural equation model based on data from the 2017 China Household Finance Survey (CHFS) and introducing its influence on households’ commercial insurance holding behavior. The results show that human capital has a significant positive effect on household commercial insurance holding behavior; financial market participation and risk preference play a part in mediating the relationship between human capital and household commercial insurance holding behavior, with financial market participation playing a greater role. According to the findings of this paper, the government and relevant institutions should increase financial literacy efforts, enhance residents’ correct understanding of commercial insurance and shape a healthy insurance market, so as to promote effective household participation in commercial insurance and the healthy development of China’s commercial insurance market.